Restrukturisasi Lampu Penerangan Jalan Umum Kampung Parigi-Sukamulya, Kec. Rumpin, Bogor - Ojak Abdul Rozak; Hedy Aditya Baskhara; Juhana Juhana (Abdimisi, 2022)
We still often hear in the media that there are fire accidents caused by leakage currents/short circuit currents and accidents due to being hit/touched by electric currents which cause injuries and even fatalities. The Indonesian government has determined that in carrying out electrical installation activities, it must comply with the General Electrical Installation Requirements (PUIL). One of the efforts to assist the government in socializing PUIL to the public in electrical installations, especially on a household (Domestic) scale and because there has never been a PUIL-standard electrical installation socialization or restructuring activity in that area, a community service activity (PkM) is planned to be located in Jl. Parigi Village, RT. 04 RW. 06, Sukamulya, Rumpin, Bogor, West Java 16350. Based on the survey that has been conducted, it was found that along the roads in the area, street lighting installations are generally not standard PUIL 2011 and have had a long service life and many have died. then a restructuring of the electrical installation must be carried out to avoid accidents due to electric shock. The method used in this PkM is to work with the local community in restructuring public street lighting installations. This is done so that people can be given knowledge about how to install electricity and immediately put it into practice. The tools and materials used to check and restructure electrical installations include: multimeters, tespen, miniature circuit breakers, lamps, cables, electrical insulation, and other supporting tools. The result of this PkM activity is that electrical installations on several power poles along roads in the area are feasible for use and in accordance with PUIL 2011.